Implementation of Character Education Through Indonesian Language Learning in Elementary Schools - Kurniawan, Dede; Rambe, Andina Halimsyah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This research aims to describe how the implementation of character values through Indonesian language learning at SDN 104298 Simpang Empat. This research uses a descriptive qualitative method. Data collection techniques in this research are observation, interview, and documentation review. Data analysis was conducted through data reduction to summarize relevant information, data presentation in the form of tables or diagrams, and conclusion drawing and verification through a triangulation process. This stage was carried out interactively until the data reached saturation, allowing the identification of supporting and inhibiting factors in the implementation of character education and formulating relevant recommendations to improve learning at SDN 104298 Simpang Empat. From this research, the results obtained are five character values that must be applied at SDN 104298 Simpang Empat, namely religious character, honesty, independence, nationalism, and social care. There are several supporting factors in the application of character, namely (1) innate, (2) personality, and (3) family. In addition to supporting factors, there are also inhibiting factors in this application, namely (1) the limited time students spend at school. (2) parents who lack time for students at home due to the busy work of parents, (3) the community environment. To overcome the obstacles in implementing character education, teachers and principals need to follow the deepening of character education. Teachers must familiarize students with the existing school culture to students. Each teacher must be able to make an assessment record of the achievement of student character values by using methods that are considered easy to learn.